Developing functionalized Fe3O4–Au nanoparticles: a physico-chemical insight1. Issue 8 (28th February 2015) - Luchini, Alessandra; Vitiello, Giuseppe; Rossi, Francesca; Ruiz De Ballesteros, Odda; Radulescu, Aurel; D'Errico, Gerardino; Montesarchio, Daniela; de Julián Fernández, César; Paduano, Luigi
<x xml:space="preserve">Abstract</x> Structural characterization and synthetic difficulties behind the obtainment of iron oxide-gold nanoparticles for biomedical applications.